2022
DOI: 10.1200/jco.2022.40.16_suppl.5567
|View full text |Cite
|
Sign up to set email alerts
|

A phase Ib study of IN10018 in combination with pegylated liposomal doxorubicin (PLD) in patients with platinum-resistant ovarian cancer.

Abstract: 5567 Background: IN10018 is a highly potent and selective oral inhibitor of focal adhesion kinase (FAK). IN10018 is synergistic with PLD against ovarian cancer in PDX models. This study evaluated the safety, tolerability, and antitumor activities of IN10018 in combination with PLD in patients with platinum-resistant ovarian cancer (PROC). Methods: This is an open-label phase Ib trial in patients with PROC (high-grade serous carcinoma only). Patient were treated with IN10018 in combination with PLD. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“… 621 IN10018 is a FAK inhibitor that showed robust efficacy in patients with platinum-resistant recurrent ovarian cancer. 622 IN10018 is under evaluation in a phase I trial in previously treated locally advanced or metastatic G/GEJ adenocarcinoma (NCT05327231). Interestingly, a recent in vivo study showed that diffuse gastric cancer with RHO-A mutations was specifically sensitive to FAK inhibitor.…”
Section: Progress In Therapies For Gastric Cancermentioning
confidence: 99%
“… 621 IN10018 is a FAK inhibitor that showed robust efficacy in patients with platinum-resistant recurrent ovarian cancer. 622 IN10018 is under evaluation in a phase I trial in previously treated locally advanced or metastatic G/GEJ adenocarcinoma (NCT05327231). Interestingly, a recent in vivo study showed that diffuse gastric cancer with RHO-A mutations was specifically sensitive to FAK inhibitor.…”
Section: Progress In Therapies For Gastric Cancermentioning
confidence: 99%
“…In the present study, we focused on a clinical-stage small molecule FAK inhibitor IN10018 (previously known as BI853520 [ 21 , 22 ]), which has obtained fast-track designation from the U.S. Food and Drug Administration (FDA) and breakthrough designation from China National Medical Products Administration (NMPA) for its combination with PLD in the treatment of platinum-resistant ovarian cancer (PROC) (clinical trial ID: NCT05551507). The previous data were reported at the 2022 ASCO annual meeting [ 23 ]. Here, we recapitulated the rationale and discovery process in identifying this regimen.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we focused on a clinical-stage small molecule FAK inhibitor IN10018 (previously known as BI853520 [20,21]), which has obtained fast-track designation from the U.S. Food and Drug Administration (FDA) and breakthrough designation from China National Medical Products Administration (NMPA) for its combination with PLD in the treatment of platinum-resistant ovarian cancer (PROC) (clinical trial ID: CTR20200913). The previous data were reported at the 2022 ASCO annual meeting [22]. Here, we recapitulated the rationale and discovery process in identifying this regimen.…”
Section: Introductionmentioning
confidence: 84%